Genomewide analysis of the Drosophila tetraspanins reveals a subset with similar function in the formation of the embryonic synapse. - Fradkin, L.G.; Kamphorst, J.T.; DiAntonio, A.; Goodman, C.S.; Noordermeer, J.N. (Proceedings of the National Academy of Sciences of the United States of America, 2002)
Tetraspanins encode a large conserved family of proteins that span the membrane four times and are expressed in a variety of eukaryotic tissues. They are part of membrane complexes that are involved in such diverse processes as intracellular signaling, cellular motility, metastasis, and tumor suppression. The single fly tetraspanin characterized to date, late bloomer (lbm), is expressed on the axons, terminal arbors, and growth cones of motoneurons. In embryos lacking Lbm protein, motoneurons reach their muscle targets, but initially fail to form synaptic terminals. During larval stages, however, functional contacts are formed. The newly available genomic sequence of Drosophila melanogaster indicates the existence of 34 additional members of the tetraspanin family in the fly. To address the possibility that other tetraspanins with functions that might compensate for a lack of lbm exist, we determined the expression domains of the Drosophila tetraspanin gene family members by RNA in situ analysis. We found two other tetraspanins also expressed in motoneurons and subsequently generated a small chromosomal deletion that removes all three motoneuron-specific tetraspanins. The deletion results in a significant enhancement in the lbm phenotype, indicating that the two additional motoneuron-expressed tetraspanins can, at least in part, compensate for the absence of lbm during the formation of the embryonic synapse.